Concede or Deny: Do Management Persuasion Tactics Affect Auditor Evaluation of Internal Control Deviations? - Wolfe, Christopher J.; Mauldin, Elaine G.; Diaz, Michelle Chandler (The Accounting Review, 2009)
ABSTRACT: In an internal control audit, the consequences and assessment subjectivity of control problems motivate managers to try to persuade auditors to lower the assessed severity of an observed control deviation. We report an experiment in which 106 audit seniors evaluate either information technology (IT) or manual control deviations that are potentially indicative of significant deficiencies, after exposure to persuasion tactics based in either concession or denial. For IT control deviations, we find that auditors assess the significance of deficiency lower and the perceived adequacy of management's explanation higher for concessions than for denials. For manual control deviations, we find no differences between concessions and denials. Our results provide evidence of a systematic bias in auditor judgment and indicate a rationale for the ubiquity of management persuasion attempts around control deviations—sometimes they work.